Tandem riser VIV suppression fairing model test - Ng, David Jinq Tyng (2014)
In deepwater development areas of Southeast Asia, the current is strong and relatively more persistent compared to other deepwater regions. Top tensioned risers (TTR) are critical submerged components of offshore platforms, constantly exposed to currents. These currents cause unsteady flow patterns around the risers i.e. vortex shedding. When the vortex shedding frequency is near the riser's natural frequency, undesirable resonant vibration of the riser also known as Vortex Induced Vibration (VIV) occurs. Several types of VIV suppression devices are used in the offshore industry. Among them, the U-shaped fairing claims to have the capabilities of reducing VIV effectively as well as lowering drag loads. This study investigates the effectiveness of a U-shaped fairing in suppressing riser VIV. The model test was successfully performed in a towing tank facility located at Universiti Teknologi Malaysia (UTM), Johor Bahru, Malaysia. This study is a significant collaboration between a local academic institution and the offshore oil and gas industry, aligned with the industry's initiative of increasing local capabilities for research and development. In this study, the VIV of two risers in tandem is simulated using scaled test models. The current flow is simulated by towing the vertically submerged test models with a moving carriage. The riser with fairing models are attached to a pair of custom-designed test rigs which are able to measure the forces and also allow movement of the test model during towing tests. The two test rigs are attached to a steel structure under the carriage which accommodates different tandem riser configurations and spacings. Two different sizes of risers and fairings are tested to check for Reynolds number effects. For each tandem riser configuration, three different riser conditions are tested, i.e. (a) bare risers without fairings; (b) risers with weathervaning fairings, and (c) upstream riser with fairing stuck at different orientations and downstream riser with weathervaning fairing. The test results show significant reduction in drag and VIV for the risers with weathervaning fairings in different tandem configurations. Interesting motion characteristics are shown in some of the stuck fairing cases highlighting the adverse effects should the fairings fail to perform normally in the field. Effective mitigation of VIV in risers using fairing suppression devices could lead to improved riser fatigue life and overall a more economical platform design. These benefits are highly applicable to local deepwater developments for the oil and gas industry.